2016
DOI: 10.1111/jfpp.12818
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Water Extract ofUrtica dioicaL. on Lipid Oxidation and Color of Cooked Pork Sausage

Abstract: The aim of this study was to determine the effectiveness of water extract and dried leaves of Urtica dioica in reducing lipid oxidation and color stabilization of cooked sausage. Four variants of sausages were prepared: control (without nettle); sausages with 300 ppm and 600 ppm water extract of nettle; and sausages with dried nettle leaves. TBARS values, color parameters, ORP, pH, aw and sensory attributes of sausages were investigated. The addition of nettle (water extract/dried leaves) did not affect the pH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…In our study, L* and a* values for the cookies enriched with nettle extract (0.2%) were the lowest compared to their counterpart fortified with hyssop and lemon balm extracts and with BHA. A similar tendency was also observed in Latocha and Stasiak [39], in which effect of nettle water extract on lipid oxidation and color of cooked pork sausage was investigated. Figure 1 presents results of sensory analysis of the cookies carried out directly after baking by a trained panel of 10 members.…”
Section: Color Measurementsupporting
confidence: 78%
See 1 more Smart Citation
“…In our study, L* and a* values for the cookies enriched with nettle extract (0.2%) were the lowest compared to their counterpart fortified with hyssop and lemon balm extracts and with BHA. A similar tendency was also observed in Latocha and Stasiak [39], in which effect of nettle water extract on lipid oxidation and color of cooked pork sausage was investigated. Figure 1 presents results of sensory analysis of the cookies carried out directly after baking by a trained panel of 10 members.…”
Section: Color Measurementsupporting
confidence: 78%
“…Bitterness of phenolic compounds present in the extracts probably reduced perceived sweetness of the enriched cookies in the same way that sweetness could mask the bitter flavor of the grape seed extract. The overall sensory quality scores of the (control) sausage with water and with dried leaves of nettle were statistically significantly lower than those for samples containing 300 and 600 ppm U. dioica extract [39]. The flavor and total acceptability of hamburger patties with lemon balm powder were also highly preferable because the fresh and sweet taste of lemon balm removed the aroma of beef and pork by acting positively on the patties [45].…”
Section: Sensory Evaluationmentioning
confidence: 93%
“…Therefore, nettle water extract can be successfully used to reduce lipid oxidation and to enhance the functionality of the final products. Other studies have investigated the use of U. dioica water extract in sucuk, a Turkish dry-fermented sausage [ 98 , 99 , 100 ], in ground beef [ 101 ], meatballs [ 102 ], in super-chilled minced meat [ 103 ], vacuum-packed beef steaks [ 104 ] and in cooked pork sausage [ 105 ].…”
Section: Food and Feed Applicationsmentioning
confidence: 99%
“…This result may be explained by the low pH value of beetroot extract and powder due to the citric acid used in the extraction, besides other components of beetroot. Latoch and Stasiak [36] reported that Urtica dioica water extract contains phenolic compounds, which contributes to lower pH values in cooked pork sausages. Baldin et al [13] also reported that the addition of 2 and 4% microencapsulated jabuticaba extract caused a reduction in the pH value of pork sausages during storage.…”
Section: Physicochemical Properties Of Sausagesmentioning
confidence: 99%